Male breast carcinoma in the oldest old: an extremely rare entity - Jagannath, Spandana; Aggarwal, Lalit; Ali, Shadan; Kumar, Ashok; Mohta, Anup (International Surgery Journal, 2020)
Male breast cancer is a rare disease and is seen in <1% of all newly diagnosed cancers in men. The present understanding of its biology, natural history, and treatment strategies is mainly based on the research findings on female breast cancer. The median age of diagnosis is 67 years. Very few cases of male breast cancer have been reported in men aged more than 70 years of age, however no case has been reported in age >85-year-old (age group now referred to as the oldest old). Risk factors include increasing age, radiation exposure, hormonal imbalance including testicular dysfunction, infertility, obesity, cirrhosis and genetic predisposition. Survival in men with breast cancer is similar to survival in women with breast cancer matched for age and stage. However, men have poor prognosis because of the more advanced stage of their cancer at the time of diagnosis. The surgical operation is usually mastectomy with axillary clearance or sentinel node biopsy. Indications for radiotherapy are similar to that for female breast cancer. Because 90% of the patients are oestrogen receptor-positive, tamoxifen is a standard adjuvant therapy, but some individuals could also benefit from chemotherapy. We report a case of male breast cancer in an 88-year-old man which is probably first in in the literature to the best of our knowledge and a brief summary of its natural history and treatment strategies are given.